PENINGKATAN KREATIVITAS BELAJAR SISWA PENDIDIKAN PANCASILA MELALUI PEMANFAATAN CANVA DI SMP KARTIYOSO SEMARANG - Yulianto, Rudi; Haryati, Titik; Sudrajat, Rahmat (FPIPSKR Universitas PGRI Semarang, 2024)
This research is motivated by the existence of low student learning creativity because in learning Pancasila Education still uses conventional learning, and has not used a variety of learning media. Based on the results of previous research, it is believed that the use of canva can be used as an interactive and effective learning media and canva can also increase learning interest and learning outcomes. The purpose of this study was to determine whether or not there was an increase in student learning creativity through the use of canva in Pancasila Education class VIII SMP Kartiyoso Semarang.This research is a quasi-experimental with the population of all students of SMP Kartiyoso Semarang. The results showed that students` creativity before using Canva was still low, with an average score of 62.However, before using Canva, students creativity was still low, with an average score of 62.However, students creativity increased after using it, with an average score of 90. Research conclusion: there is an increase in student learning creativity through the use of canva in Pancasila Education class